The Effect of Building Design on Thermal Comfort in the KONI Sports Hall, Bandung, Indonesia - Burhan Abdurrahman; Mochamad Akmal Alfarizi; Ramadona (Rumoh Journal of Architecture, 2026)
This research explores thermal comfort aspects at GOR KONI Bandung, highlighting its importance for athletes, spectators, and the community during intense physical activities. The study evaluates the current thermal conditions, measures users' comfort levels, and analyzes influencing factors such as temperature and humidity, ventilation, and user density. In addition, the study examines how building design characteristics, including the ventilation system, spatial configuration, and building envelope, contribute to the indoor thermal environment and influence users' thermal comfort. The findings indicate that an optimal thermal environment is essential in sports facilities to enhance performance and user experience. Data were collected using a quantitative approach by measuring temperature and humidity under various activity conditions. Measurements were conducted at several observation points to obtain representative thermal data and to evaluate variations in indoor environmental conditions throughout the day. Overall, the thermal conditions met WHO standards (temperature 20–28°C and humidity 40–70%), although there were significant temperature fluctuations throughout the day. Recommendations from this study include improving the ventilation system and using materials that reduce heat absorption to enhance thermal comfort. Overall, this research aims to provide solutions for creating a more comfortable environment for athletes and spectators at GOR KONI Bandung while providing practical references for the design and management of sports facilities with improved indoor environmental quality.